1-D Consolidation Characteristics of Stabilised Dredged Marine Soils as Engineered Backfills - Nor Rizan, Muhammad Affan Daniel; chan, chee ming (Progress in Engineering Application and Technology, 2026)
The Dredged Marine Soils (DMS) products that are by-products of navigational maintenance are usually considered to be geo-waste products due to their high moisture content, extreme compressibility and low shear strength. The use of such sediments as engineered backfill that could be used sustainably is becoming a more urgent requirement in order to reduce the negative environmental impact by offshore disposal and to deal with the alarming loss of inland sources of sand. Having a good feel of the one dimensional (1-D) behavior of consolidation is important to such materials, because the long-term behaviour in settlement is what directly determines serviceability to structures and adherence to high standards of infrastructure. This paper explores the possibility of regional DMS stabilization basing on bulk samples of four strategic points in Malaysian localities, namely, Kuala Kedah, Kuala Perlis, Lumut, and Endau. After physical characterization, samples were stabilized with 5% Ordinary Portland Cement (OPC) and a novel Polymer Modified Cement (PMC) 4% and then subjected to the oedometer testing, as per BS 1377: Part 5. The results obtained indicate that untreated DMS has extreme compressibility (Cc = 0.37 -0.47) and slow drainage. Although 5% OPC enhanced stiffness, it created a pore-clogging effect at high stress inhibiting consolidation. The 4% PMC treatment in contrast, demonstrated a technical breakthrough in which Cc was reduced up to 99.3% and a rigid skeleton of soil with increased consolidation rates was formed. Using simulations of performance, a 5-meter reclamation layer of PMC-treated DMS would settle within less than 10 days, with a comfortable margin of 100 mm which is the allowable settlement of the Public Works Department (JKR) Malaysia. The findings show that optimized PMC stabilization makes problematic geo-waste a high-performance, time-efficient, and sustainable resource in construction.